Losses in mechanized soybean harvest (Revista Brasileira Multidisciplinar, 2021)
Mechanized harvesting is one of the main stages of the soybean production process, however, when it is done incorrectly it causes significant grain losses. The objective of this work was to evaluate the losses in mechanized soybean harvesting under different speeds of the harvester displacement and water content of the grains. The experiment was carried out during February 2018 on a grain producing farm in the municipality of Itapaci - GO. The design used was completely randomized in a 3x3 factorial scheme, with three harvest speeds (4, 5 and 6 km h-1) and three water contents of the grains (13, 15 and 17%), with 6 replicates per treatment, totaling 54 plots spaced at 30 meters. Natural losses, losses due to deficiency in the cutting height, losses on the platform of cutting, losses in the internal mechanisms and total losses of the harvest were measured. The harvest speed factor had little influence on the occurrence of losses in this trial. Grain moisture had an influence on the occurrence of losses during mechanized soybean harvesting, especially when the grains were harvested at the highest humidity. Based on the conditions studied, the soybean harvest can be carried out with a humidity of 15% and a speed of 5 km h-1, thus providing good operational yield and reducing the time the crop remains in the field